Controllable Coordination-Driven Self-Assembly: From Discrete Metallocages to Infinite Cage-Based Frameworks - Chen, Lian; Chen, Qihui; Wu, Mingyan; Jiang, Feilong; Hong, Maochun (Accounts of chemical research, 2015)
Conspectus Nanosized supramolecular metallocages have a unique self-assembly process that allows chemists to both understand and control it. In addition, well-defined cavities of such supramolecular aggregates have various attractive applications including storage, separation, catalysis, recognition, drug delivery, and many others. Coordination-driven self-assembly of nanosized supramolecular metallocages is a powerful methodology to construct supramolecular metallocages with considerable size and desirable shapes. In this Account, we summarize our recent research on controllable coordination-driven assembly of supramolecular metallocages and infinite cage-based frameworks. To this end, we have chosen flexible ligands that can adopt various conformations and metal ions with suitable coordination sites for the rational design and assembly of metal–organic supramolecular ensembles. This has resulted in various types of metallocages including M3L2, M6L8, M6L4, and M12L8 with different sizes and shapes. Because the kinds of metal geometries are limited, we have found that we can replace single metal ions with metal clusters to alternatively increase molecular diversity and complexity. There are two clear-cut merits of this strategy. First, metal clusters are much bigger than single metal ions, which helps in the construction and stabilization of large metallocages, especially nanosized cages. Second, metal clusters can generate diverse assembly modes that chemists could not synthesize with single metal ions. This allows us to obtain a series of unprecedented supramolecular metallocages. The large cavities and potential unsaturated coordination sites of these discrete supramolecular cages offer opportunities to construct infinite cage-based frameworks. This in turn can offer us a new avenue to understand self-assembly and realize certain various functionalities. We introduce two types of infinite cage-based frameworks here: cage-based coordination polymers and cage-based polycatenanes, which we can construct through coordination bonds and mechanical bonds, respectively. Through either directly linking the unsaturated coordination sites of metallocages or replacing the labile terminal ligands with bridging ligands, we can produce infinite cage-based frameworks based on coordination bonds. We introduce several interesting cage-based coordination polymers, including a single-crystal-to-single-crystal transformation from a M6L8 cage to an infinite cage-based chain. Compared with discrete metallocages, these kinds of materials can give us higher structural stability and complexity, favoring the applications of metallocages. In addition, we discuss how we can use mechanical bonds, such as interlocking and interpenetrating, to construct extended cage-based frameworks. So far, study in this field has focused on polycatenanes constructed from M6L4 and M12L8 cages, as well as a controllable and dynamic self-assembly based on M6L4 metallocages. We also discuss cage-based polycatenanes, which can give dynamic properties to discrete metallocages. We hope that our investigations will bring new insights to the world of the supramolecular metallocages by enlarging its breadth and encourage us to devote more effort to this blossoming field in the future.